PERANCANGAN SISTEM PENUNJANG KEPUTUSAN PEMBERIAN KREDIT PADA KOPERASI BERKAH MAKASSAR - Indra Farman (Jurnal Publikasi Teknik Informatika, 2023)
System design support lending decisions on the cooperative Berkah Makassar.. the cooperative is one of the non-bank financial institutions in charge of providing public services in the form of loans and storage for the community. The aim of this study Designing and building decision support system application program lending cooperative Makassar blessing. Test program data processing applications using black box testing approach. These results indicate that this application can help the staff cooperative in lending to the applicant